Zapisz w jak najprostszej postaci;
a)4(2a-b)(2a+4b)-(3a-2b)(3b-2a)
b)2d2-(3c-2d)(c-d)-c(c-2d)+2d2
d2-d do kwadratu;) Z góry Dzięki;)))


Odpowiedź :

4(2a-b)(2a+4b)-(3a-2b)(3b-2a)
4*(4akw-4bkw)-6akw+6bkw
16akw-16bkw-6akw+6bkw
10akw+22bkw
kw- kwadrat
a)
4 * (2a - b) * (2a + 4b) - (3a - 2b) * (3b - 2a) =
4 * (4a² - 2ab + 8ab - 4b²) - (9ab - 6a² - 6b² + 4ab) =
4 * (4a² +6ab - 4b²) - (13 ab - 6a² - 6b²) =
16 a² + 24 ab - 16 b² - 13 ab + 6a² + 6b² =
22 a² + 11 ab - 10 b²

b)
2d²- (3c - 2d) * (c - d) - c * (c - 2d) + 2d² =
4d² - (3 c² - 3 cd - 2 cd + 2d²) - (c² - 2 cd) =
4d² - 3 c² + 5 cd - 2d² - c² + 2 cd =
2d² - 4 c² + 7 cd
a) 4(2a-b)(2a+4b)-(3a-2b)(3b-2a)= 8a-4b+8a-16b-9ab-6ab+6b²+2ab=16a-20b-12ab+6b²=6b²-16a-20b-13a

b) 2d²-(3c-2d)(c-d)-c(c-2d)+2d²= 2d²-3c²-3cd-2cd+2d²-c²+2cd+2d²=6d²-4c²-3cd